Kurikulum Merdeka : Fleksibilitas Kurikulum bagi Guru dan Siswa - Salsabila Ihda Alfaeni; Masduki Asbari; hilyah sholihah (Journal of Information Systems and Management (JISMA), 2023)
The aim of this study is to find out new ideas and ideas that are applied to the independent curriculum system to create fun education for students and teachers. In this study report, a descriptive qualitative method was used by taking notes because the data source was obtained by listening to the oral narrative from Guru Gembul's YouTube channel entitled "Guru Gembul Approaching Ministry of National Education, discussing the independent curriculum, misunderstandings?" which was explained by him and Mr. Anindito Aditomo, S.Psi., M.Phil., Ph.D. This research began with the low interest in reading among the public and students and the difficulty in producing the essence of a paragraph. The results of this study explain that understanding the ideal of freedom to learn is by providing learning opportunities so that students can become independent humans and lifelong students who have potential and character that is relevant for life.